Social safety net in Bangladesh: an empirical study on EGPP (Employment Generation Programme for the Poorest Poor) in santoshpur union of Nagashwari upazila under Kurigram district - Hossain, Khandokar Zakir (BRAC University, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of MA in Governance and Development, 2016.